THE ROLE OF DIFFERENTIAL EQUATIONS IN SOLVING MILITARY PROBLEMS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article discusses the possibilities of applying differential equations in solving problems related to the military sphere. Also, great attention is paid to solving military-practical problems aimed at building a mathematical model using differential equations. Using differential equations, relationships are established between the curve and its slope, the path traveled and the speed of movement.